Program adaptation by health departments - Farah Saliba, Louise; Allen, Peg; Mazzucca, Stephanie L.; Rodriguez Weno, Emily; Moreland-Russell, Sarah; Padek, Margaret; Brownson, Ross C. (Frontiers in Public Health, 2022)
Introduction The dissemination of evidence-based interventions (i.e., programs, practices, and policies) is a core function of US state health departments (SHDs). However, interventions are originally designed and tested with a specific population and context. Hence, adapting the intervention to meet the real-world circumstances and population's needs can increase the likelihood of achieving the expected health outcomes for the target population from the implemented intervention. This study identified how SHD employees decide to adapt public health programs and what influences decisions on how to adapt them. Materials and methods SHD employees (n = 45) were interviewed using a qualitative semi-structured interview guide. Telephone interviews were audio-recorded and transcribed verbatim. The transcripts were consensus-coded and themes were identified using thematic analysis. Several themes aligned with the Model for Adaptation Design and Impact. Results Data, outcomes, and health department evaluations influenced decisions to adapt a program (pre-adaptation), and reasons to adapt a program included organizational and sociopolitical contextual factors. SHD middle-level managers, program managers and staff, and local agencies were involved in the decisions to adapt the programs. Finally, the goals for adapting a program included enhancing effectiveness/outcomes, reach and satisfaction with the program; funding; and partner engagement. After SHD employees decided to adapt a program, data and evidence guided the changes. Program staff and evaluators were engaged in the adaptation process. Program managers consulted partners to gather ideas on how best to adapt a program based on partners' experiences implementing the program and obtaining community input. Lastly, program managers also received input on adapting content and context from coalition meetings and periodic technical assistance calls. Discussion The findings related to decisions to adapt public health programs provide practitioners with considerations for adapting them. Findings reaffirm the importance of promoting public health competencies in program evaluation and adaptation, as well as systematically documenting and evaluating the adaptation processes. In addition, the themes could be studied in future research as mechanisms, mediators, and moderators to implementation outcomes.